CD161+ Tconv and CD161+ Treg Share a Transcriptional and Functional Phenotype despite Limited Overlap in TCRβ Repertoire - Duurland, Chantal L.; Brown, Chrysothemis C.; O’Shaughnessy, Ryan F. L.; Wedderburn, Lucy R. (Frontiers in Immunology, 2017)
Human regulatory T cells (Treg) are important in immune regulation, but also show plasticity in specific settings. CD161 expression identifies effector-like Treg. Here we determined how CD161+ Treg relate to CD161+ conventional T cells (Tconv). Transcriptional profiling identified a shared transcriptional signature between CD161+ Tconv and CD161+ Treg, which is associated with Th1 and Th17 cells, and tissue homing, including high expression of gut homing receptors. Upon retinoic acid (RA) exposure, CD161+ T cells were more enriched for CCR9+ and integrin α4+β7+ cells than CD161- T cells. In addition, CD161+ Tconv and CD161+ Treg were enriched at the inflamed site in autoimmune arthritis, and CD161+ and CD161- Treg from the inflamed site showed suppressive capacity. CD161+ T cells from the site of autoimmune arthritis showed a diminished gut homing phenotype and blunted response to RA suggesting prior imprinting by RA in the gut or at peripheral sites rather than during synovial inflammation. TCRβ repertoires of CD161+ and CD161- Tconv and Treg from blood showed limited overlap whereas there was clear overlap between CD161+ and CD161- Tconv, and CD161+ and CD161- Treg from the inflamed site suggesting that the inflamed environment may alter CD161 levels, potentially contributing to disease pathogenesis.